Loss of CmMAIL2 compromises chloroplast function but permits developmental progression in melon - Liting Fu; Kexin Chen; Dongyang Dai; Kaihong Hu; Yuxuan Ma; Dandan Li; Yupeng Pan; Hanqiang Liu; Yunyan Sheng (Plant Science, 2026)

Transesterification for electronic-grade propylene glycol methyl ether acetate: Catalysis, deactivation & purification - Kaiqi Du; Guangpeng Chen; Hao Pan; Liting Fan; Huiping Xu; Wenqiu Su; Shaolong Wan; Wenjing Hong (Chemical Engineering Journal, 2026)

Diagnosing socioeconomic dominance in rainfall-runoff relationship changes across global basins - Xiaojing Zhang; Pan Liu; Lu Zhang; Jiabo Yin; Weibo Liu; Qian Cheng; Xiao Li; Dongyang Han; Liting Zhou; Huan Xu (Journal of Environmental Management, 2026)

Nitrogen Dominates Sedimentary Organic Carbon Distribution in a Tropical Marine Ranch - Xiaoran Shi; Liting Chen; Aiyao Yang; Yu Han; Xiaoju Pan; Zhaoyun Wang; Weijie Gong; Xiangen Wu (Journal of Marine Science and Engineering, 2026)
Marine ranching, as a pivotal strategy for enhancing the ocean’s carbon sequestration potential, offers significant potential to mitigate nearshore fishery depletion and restore marine ecosystems amid the global carbon neutrality agenda. However, the mechanistic pathways linking sediment total organic carbon (TOC) to various environmental factors in tropical marine ranches remain insufficiently quantified. This study selected the Wuzhizhou Island Marine Ranch in Hainan Province—a representative tropical marine ranch—as the research site. Field investigations and sampling were conducted during the dry (March 2024) and wet (September 2024) seasons to quantify TOC in surface sediments and associated environmental variables. A two-step analytical framework, integrating Principal Component Analysis (PCA) and Generalized Additive Models (GAM), was employed to elucidate the environmental drivers governing the spatiotemporal dynamics of TOC. The results show that the surface sediment TOC at Wuzhizhou Island Marine Ranch exhibits a distinct spatial gradient—Core Reef > Atoll > Control > Estuarine, and a pronounced seasonal pattern with elevated concentrations in the dry season relative to the wet season. The spatiotemporal differentiation of TOC is mainly driven by a gradient (explaining 52.1% of variation) that encompasses processes related to carbon accumulation from terrestrial inputs and primary production, as well as organic matter degradation promoted by nutrients and higher water temperatures. Sediment total nitrogen (TN) emerges as the primary environmental driver of TOC distribution, contributing up to 46.9% of the variance at an extremely significant level (p

Scutellaria baicalensis extract prevents metabolic dysfunction-associated steatotic liver disease by modulating the gut-liver axis in high-fat diet mice - Liting Ma; Yizhu Wang; Tao Ren; Lijia Pan; Xinze Li; Shen Wang; Dihao Li; Meiyu Zhang; Fangtong Li; Fei Zheng; Hao Yue (Phytochemistry, 2026)

Robust and efficient membrane contactor for carbon dioxide capture enabled by thin-film composite Janus membrane - Wenting Zhou; Chunlei Su; Dejun Feng; Yuanmiaoliang Chen; Liting Pan; Di He; Zhangxin Wang (ENGINEERING Environment, 2026)

A multi-pronged approach to understanding the antifungal mechanism of chitooligosaccharide against Fusarium oxysporum, a major pathogen causing potato dry rot - Airong Huang; Jie Ren; Jiaomei Zhang; Yuxin Jia; Xiaoxiao Zhou; Peidong Liu; Chunlin Zhang; Xiaoqing Huang; Xunguang Luo; Lei Shi; Liting Yang; Yujia Zhao; et al. (Postharvest Biology and Technology, 2026)

Emissions of fully fluorinated greenhouse gases in central-eastern China inferred from atmospheric observations - Qianna Du; Xiaoyi Hu; Runze Zhu; Zifa Wang; Bowei Li; Liting Hu; Zhouxiang Cai; Mingrui Ji; Jingtao Xu; Haibo Yu; Yunxing Hu; Bo Yao; et al. (Journal of Environmental Management, 2026)

Continental-scale characterization of pesticide cocktails in paddy soils: Associations with microbial community structure, function, and extracellular vesicle occurrence - Zhizhen Pan; Weiyi Wang; Wenjuan Xu; Yuhan Yin; Xueli Xu; Liting Zhu; Yifang Duan; Jingjing Lin; Diego Omar Ferraro; Rodrigo de Paula; Ehssan Torabi; Qiansheng Huang (Journal of Hazardous Materials, 2025)

Structure, transduction pathway, behavior and toxicity of fish olfactory in aquatic environments - Ning Yue; Dan Li; Yanling Pan; Liting Chen; Sisi Liu; Meifang Hou; Yongju Luo (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Identification and functional analysis of an LTR retrotransposon insertion in CsPHYB associated with early senescence in cucumber (Cucumis sativus L.) - Hanqiang Liu; Kaihong Hu; Yuxuan Ma; Liting Fu; Zeqiang Huang; Zhihui Cheng; Yuyan Sheng; Dandan Li; Yupeng Pan (Plant Science, 2025)

Unlocking efficient gold capture from electronic waste leachate with light weight hollow magnetic microspheres - Liting Luo; Hao Li; Jiazheng Zhou; Wenjie Li; Abdul Haleem; Jianming Pan (Desalination, 2025)

Chemical characterization and classification of vegetable oils using DESI-MS coupled with a neural network - Yiwei Cui; Liangcun Zhu; Yan Li; Kai Ge; Weibo Lu; Lijun Ge; Kang Chen; Jing Xue; Feiyang Zheng; Shuncong Dai; Huafei Pan; Jingjing Liang; et al. (Food Chemistry, 2025)

A versatile fluorescent probe for the ratiometric detection of hydrazine (N2H4) in water, soil, plant, and food samples - Yan Pan; Liting Tang; Lin Li; Xiongzhi Wu; Liqiang Yan (Environmental Pollution, 2024)

Polysaccharides in fruits: Biological activities, structures, and structure-activity relationships and influencing factors-A review - Liting Shi; Quan He; Jing Li; Yilong Liu; Yunlin Cao; Yaqin Liu; Chongde Sun; Yuanjiang Pan; Xian Li; Xiaoyong Zhao (Food Chemistry, 2024)

Dissecting the long-term neurobehavioral impact of embryonic benz[a]anthracene exposure on zebrafish: Social dysfunction and molecular pathway activation - Haichu Zhao; Weiran Chen; Fei Li; Xiaoyang Wang; Xin Pan; Yang Liu; Liting Wang; Wei Sun; Fei Li; Shan Jiang (Science of The Total Environment, 2024)

Clinical report and genetic analysis of a novel variant in ZMIZ1 causing neurodevelopmental disorder with dysmorphic factors and distal skeletal anomalies in a Chinese family - Liting He; Yao Wang; Jiahua Pan; Limin Guo; Haoquan Zhou; Lan Zhang (Genes & Genomics, 2024)

Time-varying parameters from the same period in previous years to improve runoff forecasting - Xiaojing Zhang; Pan Liu; Lei Cheng; Liting Zhou; Weibo Liu; Xinran Luo (Journal of Hydrology, 2024)

Antibiotic resistome and associated bacterial communities in agricultural soil following the amendments of swine manure–derived fermentation bed waste - Zhizhen Pan; Zheng Chen; Liting Zhu; Ricardo David Avellán-Llaguno; Bo Liu; Qiansheng Huang (Environmental Science and Pollution Research, 2023)

Simvastatin-enhanced bioinspired exosome mimetics regulate osteogenesis and angiogenesis for the treatment of glucocorticoid-induced osteonecrosis of the femoral head - Hongyi Jiang; Chao Lou; Liting Jiang; Chihao Lin; Weidan Wang; Zijian Yan; Jiachen Yu; Tingwen Cai; Shida Lin; Jilong Wang; Xiaoyun Pan; Xinghe Xue (Chemical Engineering Journal, 2023)

Improving structure identifiability of hydrological processes by temporal sensitivity with a flexible modeling framework - Liting Zhou; Pan Liu; Xiaojing Zhang; Lei Cheng; Qian Xia; Kang Xie; Weibo Liu; Jun Xia (Journal of Hydrology, 2023)

Mechanisms of cardiovascular toxicity induced by PM2.5: a review - Tianyang Zhao; Wen Qi; Pan Yang; Liwei Yang; Yanbin Shi; Liting Zhou; Lin Ye (Environmental Science and Pollution Research, 2021)

Dry-wet variations and cause analysis in Northeast China at multi-time scales - Qi Hu; Feifei Pan; Xuebiao Pan; Liting Hu; Xiaoxiao Wang; Pengyu Yang; Pei Wei; Zhihua Pan (Theoretical and Applied Climatology, 2018)